Effects of biogenic CBM generation on microcrystalline and functional groups of high-volatile bituminous coal - Aikuan Wang; Qiang Huang; Zhiyuan Yao (Heliyon)
Understanding the biogenic mechanism of coalbed methane (CBM) requires a deep exploration of the physical and chemical changes that occur in organic matter during the biodegradation process. The present research employs four samples of high-volatile bituminous coal, which were obtained from the Huainan Coal Mine located in Anhui Province, China. The samples serve a purpose in a simulation experiment aimed at investigating the generation of biogenic CBM. In the course of the experiment, X-ray diffraction (XRD) analysis is employed to examine the coal microcrystal structures, whereas Fourier transform infrared (FTIR) spectroscopy serves for the analysis of the chemical structures. The experiment conducted through simulation extended over a period of 80 days, during which the average rate of biogenic CBM generation was measured at 7.43 mL/g. Based on the experimental conditions, it appears that high-volatile bituminous coal shows potential for biogenic applications. XRD results also prove that the distance between aromatic layers (d002) increased slightly, while the degree of extension (Lc), stacking (La), and the number of accumulated layers (Nc) decreased, indicating that the coal microcrystalline structure damaged due to the biodegradation. Based on the FTIR analysis, there was a decrease in the levels of aliphatic hydrocarbon and methyl functional groups, while the presence of functional groups containing hydroxyl and oxygen increased. The findings suggest that chain hydrocarbons significantly impact the early stages of biodegradation. The byproducts generated during this process have the potential to disrupt the microcrystalline structure of coal.